(untitled) - Hoynden, Yoshio (Asia, 1954)
This book introduce the coal mining industry, the non-ferrous metal industry, thw iron and steel industry, the shipbuilding industry, the machinery industry, the chemical industry...
Keywords: Chính sách công nghiệp,Industrial policy; Nhật Bản,Japan